Polysome turnover in immobilized cells of Nostoc commune (cyanobacteria) exposed to water stress. - Angeloni, S V (1986)
Water stress induced changes in the polysome content of immobilized cells of the desiccation-tolerant cyanobacterium Nostoc commune UTEX 584. Cells maintained an intact protein synthesis complex during 2 h of drying at -99.5 MPa. Polysomes were not recovered from cells subjected to extended periods of desiccation.